Upad populacije in sprememba rabe tal v lovnem habitatu rjavega srakoperja Lanius collurio v Šturmovcih (SV Slovenija) - Denac, Damijan (Acrocephalus, 2003)
In 1997 and 2003, pairs of Red-backed Shrike Lanius collurio were censused in the Šturmovci area, primarily alluvial floodplain forest that was eventually transformed into pastures and meadows with numerous trees, solitary shrubs andhedges. It is located 7 km SE of Ptuj (UTM WM73, NE Slovenia) . The area count method, a simplified mapping method, was applied. The mapped area covered 4.4 km2. In both years, data on Red-backed Shrike's hunting habitats were gathered, while in 2003 data on perching site types and their heights were also collected. In 1997, 89 pairs were counted (density 20.5 pairs/km2), while in 2003, 53 pairs were recorded (density 12.2 pairs/km'). Between 1992, when the first census was carried out by STUMBERGER et al. (I993), and 2003 the breeding pair population declined by 69%. In 2003, the highest breeding density in 1 km2 square was 23.3 pairs. Most Red-backed Shrikes hunted in meadows, 88% in 1997 and 60% in 2003. Most of those that hunted in meadows, did so in mown meadows: 72% in 1997 and 57% in 2003. The highest perching sitewas 10 m, the lowest 0.5 m from the ground. Average height of perching sites was 2.6 +- 1.8 m. The highest perching sites were found in overgrowing habitat. Disappearance of meadows due to intensive farming and cessation of mowing are the main causes for the Redv backed Shrike's population decline at Sturmovci.
Keywords: Birds; Ekosistem; Gnezdenje živali; Ecosystem; Agriculture; Poljedelstvo; Ptice; bird; Nesting Behavior; Behavior, Animal; Vedenje živali; ornitologija; rjavi srakoper